Equity in Health and Health Care in the Philippines - Hyun Son (Asian Development Bank (ADB), 2009)
Equity is an abstract concept covering philosophical issues such as fairness and social justice, making its definition and measurement very complex. This study attempts to define and measure equity in health status and health care utilization using the equity index of opportunity. The study introduces a methodology to explain equity in terms of between- and within-group equity. While the between-group equity implies equal treatment for equal needs, the within-group equity implies that individuals with unequal needs should be treated unequally according to their different needs. The proposed methodology can be applied to any socioeconomic and demographic group. Empirical analysis is carried out using Demographic and Health Surveys and Annual Poverty Indicator Surveys conducted in the Philippines.
hdl:11540/1822
Keywords: 330